Chemiluminescence-based immunoassay for the detection of heroin and its metabolites - Singh, S.; Mishra, P.; Banga, I.; Parmar, A.S.; Tripathi, P.P.; Gandhi, S. (Tabriz University of Medical Sciences, 2018)
Introduction: Continuous use of opiates causes drug-related illnesses, which poses an alarming situation to develop sensitive detection platform. In this study, a highly sensitive and reliable chemiluminescence immunoassay (CI) has been developed for the detection of heroin and its major metabolites in spiked urine samples. Methods: To develop robust immunoassay, monoacyl morphine-bovine serum albumin (MAMBSA) conjugate was synthesized and characterized thoroughly by physicochemical techniques. The anti-MAM antibodies were developed, labeled with horseradish peroxidase (HRP) and immunoassay was developed to detect the presence of target drug in spiked urine samples. Results: A competitive CI was developed, where heroin, MAM, morphine, and codeine concentration were ranged from 0-1000 ng/mL in spiked urine samples and the limit of detection were 80, 95, 90, 75 pg/ mL. Conclusion: The developed CI is highly sensitive, specific, point of care, cost-effective and can be used as a routine technique for quantitative analysis for screening of narcotic drugs. © 2018 The Author(s).
Keywords: Monoacetyl morphine; Metabolites; Chemiluminescence immunoassay; Antibody; Horseradish peroxidase